Distal femoral fractures: The need to review the standard of care. Issue 6 (June 2015) - Smith, James R.A.; Halliday, Ruth; Aquilina, Alexander L.; Morrison, Rory J.M.; Yip, Grace C.K.; McArthur, John; Hull, Peter; Gray, Andrew; Kelly, Michael B.; ,
Abstract: Background: Hip fracture care has evolved, largely due to standardisation of practice, measurement of outcomes and the introduction of the Best Practice Tariff, leading to the sustained improvements documented by the National Hip Fracture Database (NHFD). The treatment of distal femoral fractures in this population has not had the same emphasis. This study defines the epidemiology, current practice and outcomes of distal femoral fractures in four English centres. Patients and methods: 105 patients aged 50 years or greater with a distal femoral fracture, presenting to four UK major trauma centres between October 2010 and September 2011 were identified. Data was collected using an adapted NHFD data collection tool via retrospective case note and radiograph review. Local ethics approval was obtained. Results: Mean age was 77 years (range 50–99), with 86% female. 95% of injuries were sustained from a low energy mechanism, and 72% were classified as either 33-A1 or 33-C1. The mean Parker mobility score and Barthel Independence Index were 5.37 (0–9) and 75.5 (0–100) respectively. Operative management was performed in 84%, and 86% had their surgery within 36 h. Three quarters were fixed with a peri-articuar locking plate. There was no consensus on post operative rehabilitation, but no excess of complications in the centres where weight bearing as tolerated was the standard. 45% were seen by an orthogeriatrician during their admission. Mean length of stay was 29 days. Mortality at 30 days, 6 months, and 1 year was 7%, 16% and 18% respectively. Discussion: This study demonstrates that the distal femoral and hip fracture populations are similar, and highlights the current disparity in their management. The metrics and standards of care currently applied to hip fractures should be applied to the treatment of distal femoral fractures. Optimal operative treatment and rehabilitation remains unclear, and is in need of further research.